National Consensus on the Management of Gastroesophageal Reflux Disease in Indonesia - The Indonesian Society of Gastroenterolo The Indonesian Society of Gastroenterology (Acta Medica Indonesiana)
Gastroesophageal reflux disease (GERD) is a disorder, which gastric content repeatedly reflux into the esophagus causing disturbing symptoms and/or complications. Various epidemiological studies show that there is regional difference on the aspect of prevalence and clinical manifestation. Regional data also demonstrates increased incidence of complications such as the Barret’s Esophagus and adenocarcinoma. In response to the situation, the Asia-Pacific GERD experts, including Indonesia, had published a consensus on the management of GERD in 2004, which was subsequently revised in 2008. Advances in medical technology, especially on gastrointestinal endoscopy technique and other diagnostic instruments such as 24-hour pH-metry and manometry, have improved the capacity of management of GERD. On the other hand, we feel that adequate knowledge and skills of doctors, both for general physicians and specialists of internal medicine in our country are not well-distributed. Moreover, the availability of instruments for diagnostic and therapeutical supports differs from one region to the others. The Organizing Committee of Indonesian Society of Gastroenterology or Pengurus Besar Perkumpulan Gastroenterologi Indonesia (PB PGI) considers that it is important to revise the National Consensus on the Management of GERD in Indonesia 2004, which is expected to be the guideline of GERD management.